POKOK-POKOK DALAM ANALISA MIKROBIOLOGI PANGAN*) Sebuah Tinjauan - Milono Poesponegoro (Jurnal Kimia Terapan Indonesia, 1997)
Microorganisms in foods not only can deteriorate the quality and shelf life of foods, but also capable of producing food poisoning. Therefore, microbiological analysis of foods is essentia, particularly to establish safety, to secure adequate microbiological quality and for standardization of food products.The existence of microbial pollution in foods needs standard microbiological analysis of foods to obtain accurate results of analysis. This is due to the fact that beside the complex nature of foods, the number of factors affecting the results of analysis are innumerable such as food age, sampling methods and treatment of the samples, and the methods of analysis used. In framing me/hods for the microbiological analysis of foods consideration must be given not only to the phycical and chemical properties of the food, but also to the form of processing they have recieved, the types of pathogens or spoilage organisms likely to be of most importance and the number likely to be present. This paper presents a review on the fundamentals of microbiological analysis of foods to clarify the various microbiological aspects, background and the principles outlay the works of microbiological analysis offoods and their problems.This paper presents a review on the fundamentals of microbiological analysis of foods to clarify the various microbiological aspects, background and the principles outlay the works of microbiological analysis of foods and their problems.